Implementasi Literasi Sekolah Dalam Meningkatkan Minat Baca Peserta Didik - Lilis Santika Lilis Santika; Moh Toharudin; Mu’amar Mu’amar (Peneliti.net, 2022)
This study aims to describe the impact of school literacy programs on students' interest in reading. This research employs a qualitative, case-studybased methodology. In this study, the informants or subjects were third graders from SD Negeri Klampok 02, a total of ten students with categories in increasing students' reading interest and one class teacher. The ability of students during reading literacy activities is a crucial first step in the success of the learning process in this activity. Because with proficient reading skills, students will have a strong memory and access to a wealth of information from a variety of sources.